Խնդրի տիպավորման հարցը (անգլերենի նյութի հիման վրա հայերենի զուգադրությամբ - Մերի Վարդանյան (ՀՀ ԳԱԱ հրատ.)
The typological classification of objects in English and Armenian is based on different principles and criteria. In English the classification is based priniarily on the syntactic-morphological principle, due to which English distinguishes three types o f objects: direct, indirect (prepositional and nonprepositional) and complex object. There is no complex object in Armenian; the English complex object is rendered in Armenian by means of an object-subordinate clause. However, unlike English, the classification of objects in Armenian is based not only on the syntactic-morphological principle, but also on the semantic criterion, which leads to further classification of the direct and indirect object into numerous semantic subgroups. In both the languages the object is used with finite as well as non-finite forms of the verb.
Keywords: Philology; Linguistics; Language and Literature